KATA DAN MAKNA HIJRAH DALAM PRESPEKTIK GENERASI MILENIAL - Siti Mahmudah Yanti (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2019)
The purpose of this study is to describe the meaning of jihad according to religionin the prespective of millennial generation. This type of research is qualititativewith descriptive analysis method.Data collection was carried out by theresearchers themselves.The data is taken through direct observation in the town ofLamongan and its surroudings with a phenomonological approach and uses aninterpretive paradigm by building understanding of reality. Rosulullah SAWsaid,with means “ and al muhajjir (people who emigrate) are those who leave theprohibition of Allah SWT ”. According to the big dictionary of Indonesialanguage Muhajjir is a person who moves or is displaced. The perspektive oftoday’s millennial generation is more constructive as a change in self orobediensce for the better in front of Allah SAW.